The millipede genus Chamberlinius (Diplopoda, Polydesmida, Paradoxosomatidae) in mainland Southeast Asia, with the description of a new species from Laos - Likhitrakarn, Natdanai; Lips, Josiane; Golovatch, Sergei I.; Panha, Somsak; Sutcharit, Chirasak (Zootaxa, 2026)
The Southeast Asian millipede genus Chamberlinius Wang, 1956, has been known only from Taiwan, southern Japan, and recently from central Vietnam. This paper describes a new species, Chamberlinius laoticus sp. nov., from a limestone cave in Khammouane Province, Laos, representing the second known mainland representative from Indochina. The new species is readily distinguished from all congeners by its smaller size, uniformly pale coloration lacking any darker markings, and the absence of ridge-like spiracles flanking the gonopod aperture. This warrants the generic diagnosis to be slightly amended. An updated key to and a distribution map for all seven known species of Chamberlinius are also provided.